Issues of photographic works by copyright norms - Омельченко, Г. В.; Вітковська, Ю. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article an authors analyzea an approaches of the understanding of the photographic work and thecontent of legal norms of regulation of social relations in the process of creation and using of thephotographic works, also in the sphere of digital environment.